2000
DOI: 10.1046/j.1471-4159.2000.0752611.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Labeling of Mitochondrial Complex I (NADH:UbiquinoneOxidoreductase) in Rat Brain Using [3H]Dihydrorotenone

Abstract: Defects in mitochondrial energy metabolism have been implicated in several neurodegenerative disorders. Defective complex I (NADH:ubiquinone oxidoreductase) activity plays a key role in Leber's hereditary optic neuropathy and, possibly, Parkinson's disease, but there is no way to assess this enzyme in the living brain. We previously described an in vitro quantitative autoradiographic assay using [ 3 H]dihydrorotenone ([ 3 H]DHR) binding to complex I. We have now developed an in vivo autoradiographic assay for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 39 publications
0
57
0
1
Order By: Relevance
“…1 After systemic administration of 2 to 3 mg/kg per day, the concentration of free rotenone in the brain is approximately 20 to 30 nmol/L. 4,5 In addition, Talpade et al 4 suggested that 1 to 30 nmol/L of rotenone may be a reasonable concentration in the living rat brain under rotenone-triggered pathological conditions. Based on these reports, we used 1 to 30 nmol/L of rotenone in our present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 After systemic administration of 2 to 3 mg/kg per day, the concentration of free rotenone in the brain is approximately 20 to 30 nmol/L. 4,5 In addition, Talpade et al 4 suggested that 1 to 30 nmol/L of rotenone may be a reasonable concentration in the living rat brain under rotenone-triggered pathological conditions. Based on these reports, we used 1 to 30 nmol/L of rotenone in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is a highly lipophilic pesticide that readily crosses the bloodbrain barrier and accumulates throughout the brain. 4,5 Rotenone exposure has disrupted cell membranes and caused damage to proteins, lipids, and DNA, ultimately leading to neuronal cell death. Indeed, there is increasing evidence that long-term exposure to rotenone causes significant degenerative diseases.…”
mentioning
confidence: 99%
“…Due to its lipophilic character, rotenone crosses membranes freely and accumulates in cytoplasm and mitochondria [27] where it inhibits complex I of the mitochondrial respiratory chain by stopping the supply of electrons to quinol (OH 2 )-cytochrome c oxireductase [28]. This results in a dosedependent ATP-depletion, generation of free radicals, and finally apoptosis [29].…”
Section: Introductionmentioning
confidence: 99%
“…Rotenone is an agricultural chemical, which was originally employed by Indians as a fish poison, and today it is a commonly used pesticide and is also used in lakes and reservoirs to kill fish that are perceived as pests. Rotenone is extremely lipophilic, which makes it penetrate all cell types and move freely across cellular membranes independent of any reuptake transport mechanism [Talpade et al, 2000]. More importantly, rotenone easily crosses the blood-brain-barrier, enters the brain rapidly, and accumulates in subcellular organelles, such as mitochondria [Higgins & Greenamyre, 1996; Bertabet et al, 2000; Talpade et al, 2000], where it impairs oxidative phosphorylation by inhibiting complex I, also known as NADH-ubiquitinone reductase, the first enzyme complex of the electron transfer chain [Schuler & Casida, 2001; Sherer et al, 2003a].…”
Section: Introductionmentioning
confidence: 99%